Application of Design Thinking (Double Diamond Framework) and Optimization Methods for Optimizing the Supply Chain of Multinational Cigarette Companies Using Value Stream Mapping Tools - Lomarga, Zefano Valery (Journal of Applied Sciences, Management and Engineering Technology, 2025)
This research examines the supply chain optimization strategy of a UK-based multinational cigarette company with manufacturing plants in Indonesia, with a primary focus on improving operational efficiency and sustainability through the application of a Design Thinking approach using the Double Diamond framework, optimization methods, and Value Stream Mapping (VSM) tools. The project is aimed at addressing a number of complex challenges in the supply chain, including high material costs, manufacturing inefficiencies, SKU complexity, and distribution and logistics inefficiencies. With the selection of a strategic end-country market that contributes more than 25% of the company's total volume (worth GBP 5 million in working capital), a thorough mapping of the current process and waste identification was carried out using a lean approach. The Discover and Define stages were used to explore the root causes through fishbone analysis and VSM, while the Develop stage designed solutions based on optimization methods such as Greedy Algorithm for material procurement, Simulated Annealing for production scheduling, and Mixed Integer Linear Programming (MILP) for logistics and transportation. The implementation of the Deliver phase solution resulted in production cost savings of more than GBP 2 million, cash flow release of GBP 15 million, improved customer service, and carbon emission reduction of up to 10%. The study confirms that the integration of Design Thinking approach, optimization methods, and Lean-Circular principles can improve operational efficiency and meet sustainability targets in a measurable and applicable manner.